TCAD investigation on hot-electron injection in new-generation technologies. (September 2018) - Reggiani, S.; Rossetti, M.; Gnudi, A.; Tallarico, A.N.; Molfese, A.; Manzini, S.; Depetro, R.; Croce, G.; Sangiorgi, E.; Fiegna, C.
Abstract: The hot electron injection model presently available in the TCAD tools has been investigated against experiments on new test devices to the purpose of gaining an insight on its predictability in the context of the new-generation technologies. The study has been carried out on electron emission in extremely high electric fields, as expected in power LDMOS devices at the onset of avalanche breakdown, reaching for the first time injection probabilities as high as 0.01. The numerical analysis clearly showed that the new Si/SiO2 interfaces experience different features with respect to the old ones. The TCAD method based on the deterministic solution of the Boltzmann equation can accurately capture such effects.